A Comparison of Outcomes Using Combined Intra- and Extradural versus Extradural-Only Repair of Tegmen Defects - Khanna, Omaditya; D'Souza, Glen; Hattar-Medina, Ellina; Karsy, Michael; Chiffer, Rebecca C.; Willcox, Thomas O.; Farrell, Christopher J.; Evans, James J. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective Tegmen tympani or tegmen mastoideum defects involve dehiscence of the temporal bone that can be a source of cerebrospinal fluid (CSF) otorrhea. Herein, we compare a combined intra-/extradural repair strategy with an extradural-only repair as it pertains to surgical and clinical outcomes.Design A retrospective review from our institution was performed of patients with tegmen defects requiring surgical intervention.Participants Patients with tegmen defects who underwent surgery (combined transmastoid and middle fossa craniotomy) for repair of tegmen defects between 2010 and 2020 were inclined in this study.Results A total of 60 patients with 40 intra-/extradural (mean follow-up time: 1,060 ± 1,103 days) and 20 extradural-only (mean follow-up time: 519 ± 369 days) repairs were identified. No major differences in demographic factors or presenting symptoms were identified between the two cohorts. There was no difference in hospital length of stay between the two patient cohorts (mean: 4.15 vs. 4.35 days, p = 0.8). In the extradural-only repair technique, synthetic bone cement was more frequently used (100 vs. 7.5%, p < 0.01), whereas in the combined intra-/extradural repair, synthetic dural substitute was used more often (80 vs. 35%, p < 0.01), with similar successful surgical outcomes achieved. Despite disparities in the techniques and materials used for repair, there were no differences in complication rates (wound infection, seizures, and ossicular fixation), 30-day readmission rates, or persistent CSF leak between the two treatment cohorts.Conclusion The results of this study suggest no difference in clinical outcomes between combined intra-/extradural versus extradural-only repair of tegmen defects. A simplified extradural-only repair strategy can be effective, and may reduce the morbidity of intradural reconstruction (seizures, stroke, and intraparenchymal hemorrhage).
Keywords: tegmen tympani; tegmen mastoideum; cerebrospinal fluid leak; mastoidectomy; otorrhea; intracranial hypertension